Adsorption characteristics and behavior of a graphene oxide–Al13 composite for cadmium ion removal from aqueous solutions. Issue 83 (9th September 2015) - Yan, Lu; Zhao, Qian; Jiang, Tingshun; Liu, Xiufang; Li, Yingying; Fang, Weibing; Yin, Hengbo
<x xml:space="preserve">Abstract</x> Graphene oxide–Al13 (GO–Al13) composites were synthesized by a hydrolysis method on the basis of graphite oxide and were characterized by XRD, FT-IR and SEM.